2014
DOI: 10.1159/000366486
|View full text |Cite
|
Sign up to set email alerts
|

Executive Impairment Predicts Schizophrenia Diagnosis and Treatment Status in Mid-Term Follow-Up of Early-Onset Psychosis

Abstract: Objectives: Early-onset psychoses (EOP) vary considerably with regard to diagnostic stability and functional outcome. The aim of this study was the assessment of executive dysfunction as a predictor of outcome in EOP. Method: This was a retrospective cohort study. Twenty-five hospitalized patients with non-affective EOP were assessed with the Wisconsin Card Sorting Test (WCST) during the index admission. Associations with current diagnosis, further admissions, current treatment status and occupational and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For instance, the study of Albert et al [ 29 ] revealed that worse childhood executive functions (EFs) are predictive of greater prodromal symptoms of psychosis in young adulthood. Also, in the retrospective cohort study of Rembark et al [ 30 ], baseline executive function impairment was associated with a schizophrenia diagnosis and psychiatric treatment at follow-up. At the same time, in another study [ 17 ], executive functions show the largest impairments in different “at-risk” groups, although they do not predict a later transition to psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the study of Albert et al [ 29 ] revealed that worse childhood executive functions (EFs) are predictive of greater prodromal symptoms of psychosis in young adulthood. Also, in the retrospective cohort study of Rembark et al [ 30 ], baseline executive function impairment was associated with a schizophrenia diagnosis and psychiatric treatment at follow-up. At the same time, in another study [ 17 ], executive functions show the largest impairments in different “at-risk” groups, although they do not predict a later transition to psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a hypofunction of the dopamine system in the ACC (Abi‐Dargham & Moore, 2003; Chen et al, 2016; MacKenzie et al, 2018; McCutcheon et al, 2020). The increased susceptibility to distraction has been linked to poor psychosocial measures, and a generally impaired quality of life (Fehnel et al, 2016; Friedman et al, 2018; Michl et al, 2013; Remberk et al, 2014). As current pharmacotherapies for ADHD (Bioulac et al, 2020; Pitzianti et al, 2020) and major depression (Mallet et al, 2019) typically increase dopamine levels in the brain but fail to alleviate distractibility, more research is needed to understand the specific contributions of the ACC to distractibility.…”
Section: Introductionmentioning
confidence: 99%